HUBUNGAN POLA ASUH DAN TINGKAT PENDAPATAN EKONOMI ORANGTUA DALAM PENINGKATAN STATUS GIZI ANAK BALITA PADA MASA PANDEMIC COVID-19 DI DESA BARAKATI KECAMATAN BATUDAA KABUPATEN GORONTALO - Muriyati Rokani; Andi Akifa Sudirman; Nur Ainnun K. Uba; Sri Yulianti Amara (Jurnal Rumpun Ilmu Kesehatan, 2021)
Nutritional status is an expression of a state of balance in the form of certain variables or the manifestation of nutrition in the form of certain variables. The purpose of this study was to determine the relationship between parenting style and the level of parents’ economic income in improving the nutritional status of toddler during the COVID-19 pandemic in Barakati Village, Batudaa District, Gorontalo Regency. The research design used an analytical survey method with a cross sectional approach. the sampling technique uses purposive sampling. The results showed that there is a relationship between parenting style and the level of parents’ economic income during the COVID-19 pandemic with the nutritional status of toddler. The conclusion is that the majority of parents apply directive parenting with a low level of parental income, but this does not make parents’ attention to child nutrition neglected so that the average nutritional status of children is normal. Suggestions from this study are that parents can provide good parenting to children and pay attention to the nutritional status of children by utilizing food ingredients that are easily available but have good nutritional content.